Television Media and Children: A Sociological Insight on Rural Society in Punjab - Dr. Mani Inderpal Singh (International Journal of Children, 2026)
The present paper deals with to understand the media forms of television and digital media as an influential agent of socialisation in contemporary society, especially among the children. The increasing accessibility of television and digital media, especially in the rural society of Punjab, have greatly impacted the patterns of childhood socialisation, cultural norms, religious practices, attitudes, and routine behaviour. During the study it is found that television continues to occupy a central place in children’s everyday life especially in the village society in Punjab, despite the growth of digital media technologies. The present study also highlights that how language, lifestyle, ways of dealing and expressing, consumption patterns, and social attitudes of rural children shaped under the influence of television and digital media. The study also highlights the growing influence of cartoons and other entertainment programmes, social media content and advertisements on their overall behaviour and choices. Children try to imitate the language, expressions, communication styles, behavioural patterns as portrayed on television showing children’s programmes having different cartoon characters, digital influencers and television personalities. The characters shown over the media often become the role models and heroes for the children influencing their perception, aspirations, interactions, and creating understanding towards the life. The media exposure also influences the children by creating their sense of clothing, food habits, toys, brands, merchandise and leisure activities. Advertisement and digital content inculcate the value of consumerism among the young generation, as the media content create new desires and demands within rural population. The study is theoretically drawn under the framework of Pierre Bourdieu, as we try to understand our problem in the light of the concepts given by Bourdieu i.e. the concept of habitus, cultural capital, social capital and symbolic power to understand that how media contributes to the formation of the cultural orientations and social behaviour among the rural children. Media as cultural institution has introduced the rural children with urban lifestyles, the market-oriented values, and new forms of social. The study tries to create an understanding towards the changing nature of childhood under the influence of television and digital media, and an attempt has been made to understand family relations, cultural identity, language patterns, and rural social structure in the light of modern television media. Therefore, the study tries to understand the contribution of television media in shaping contemporary rural childhood.
Keywords: Children; Television; advertisements; cartoon; consumerism; consumption patterns; language pattern; socialisation